A comparison of muscle activity, posture and body discomfort during the use of different computer screen sizes. Issue 1 (2nd January 2023) - Sengsoon, Praphatson; Siriworakunsak, Kanruethai
Abstract : This study aims to compare changes in neck angles, muscle activities, ergonomic risk and body discomfort caused by use of two different computer screen sizes. The 36 female users who participated used displays with 46.99 and 58.42-cm screen sizes and were assessed for craniocervical angle (CCA), craniovertebral angle (CVA), upper trapezius (UT) and sternocleidomastoid (SCM) muscle activity, ergonomic risk and body discomfort for a duration of 1 h. The results showed there were no significant differences when comparing usage between both computer screen sizes ( p  > 0.05). However, there were significant differences in the CCA, UT muscle activity and body discomfort when comparing before and after usage for both computer screen sizes ( p  < 0.05). The results indicate that computer users can select different screen sizes for working but should be concerned with neck angle, muscle activity and body discomfort when using for long periods of time.